Acres and acres [videorecording (DVD)] - Johnson, Niall; Spall, Rafe, 1983-; Fox, Emilia, 1974-; Cassidy, Elaine, 1979-; Stagg, William; Stagg, Matthew; Greene, St John (Gravitas Ventures, 2019)
The heartwarming story of Singe and Kate, a couple from north Somerset, whose lives were turned upside down when Kate was diagnosed with incurable breast cancer. Over her last few days, she created her list and wrote her thoughts and memories down to help the man she loved create the best life possible for their two sons after she was gone.